Enhancing TreeMMoSys with a high-precision strain gauge to measure the wind-induced response of trees down to the ground - Julius Nickl; Sven Kolbe; Dirk Schindler (HardwareX, 2022)
Measuring tree response to wind loads is fundamental for the process-based analysis of wind-tree interactions. Comprehensive knowledge of wind-tree interactions enables the further development of decision support tools available for estimating the probability of wind damage to trees. The assessment of critical wind loads that lead to damage is particularly important. This paper describes the inexpensive Tree Strain Sensor (TSS) suitable for precisely measuring the response of tree parts to external loads such as pulling tests and natural wind loading. It is an addition to the recently developed Tree Motion Monitoring System (TreeMMoSys) but can also be used as a standalone device, allowing measurements necessary to estimate effective wind loads on trees.